2021
DOI: 10.1111/grs.12326
|View full text |Cite
|
Sign up to set email alerts
|

Common response of dominant plants in typical grassland of Inner Mongolia to long‐term overgrazing revealed by transcriptome analysis

Abstract: Leymus chinensis (Trin.) Tzvel. and Stipa grandis P. Smirn. are dominant species in grassland on the typical steppe of Inner Mongolia. Long‐term overgrazing, which is considered to represent multiple stresses, reduces the growth of L. chinensis and S. grandis. To gain an understanding of the molecular mechanisms underlying the responses of these plants to overgrazing, we explored the gene expression profiles of L. chinensis and S. grandis to discover the common features of these dominant plants in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 91 publications
(138 reference statements)
0
3
0
Order By: Relevance
“…In our study, HRW response to cold stress was also mainly related to the enrichment of biosynthetic pathways mentioned above and regulation of related gene families, including PAL, CHS, COMT, AtBG1, and IF7MAT. Under long-term overgrazing and cold stress, PAL expression of Leymus chinensis ( Wan et al, 2021 ) and T. hemsleyanum ( Peng et al, 2019 ) was significantly upregulated. In our study, cold stress also significantly upregulated the expression of PAL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, HRW response to cold stress was also mainly related to the enrichment of biosynthetic pathways mentioned above and regulation of related gene families, including PAL, CHS, COMT, AtBG1, and IF7MAT. Under long-term overgrazing and cold stress, PAL expression of Leymus chinensis ( Wan et al, 2021 ) and T. hemsleyanum ( Peng et al, 2019 ) was significantly upregulated. In our study, cold stress also significantly upregulated the expression of PAL.…”
Section: Discussionmentioning
confidence: 99%
“…( Singh and Kumaria, 2020 ). For example, CHS expression was significantly upregulated in both Leymus chinensis and maize, under long-term overgrazing ( Wan et al, 2021 ) and cold stress conditions ( Páldi et al, 2014 ). In the present study, T. hemsleyanum also showed upregulation of CHS expression under cold stress.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic analysis of cloned L. chinensis showed that grazing had a transgenerational effect on its growth inhibition and led to the development of a dwarf phenotype in response to the severe degradation of the grassland habitat due to heavy grazing [ 23 ]. In addition, transcriptomic analysis of overgrazed L. chinensis showed that most differentially expressed genes (DEGs) were significantly enriched in phenylpropanoid biosynthesis and flavonoid biosynthesis pathways [ 24 ]. Therefore, through the analysis of omics, we can find relevant DEGs, differentially expressed metabolites (DEMs), and other information, enabling the identification of key metabolic pathways, pinpointing the crucial metabolic response mechanisms and identification of the causal genes.…”
Section: Introductionmentioning
confidence: 99%